Análise das competições de base no futebol: influência dos formatos de jogo sobre o desempenho físico e comportamento tático em categorias sub-11 - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
To adjust the context of children's competition to the players' needs, several federations have proposed changes in the game's structural references. Understanding the importance of providing young players with competitive contexts that are representative and adjusted to the intrinsic dynamics of the players, this dissertation aimed to investigate how different competition contexts impact the physical and tactical performance, as well as the dynamics of spatial occupation of players in the U-11 age category. In Chapter I, the individual and collective actions of a team was observed in order to investigate the influence of the 5-a-side football (F-5), 7-a-side football (F-7), and 11-a-side football (F-11) formats on the technical- tactics, physics and on the dynamics of space occupation in a simulated competition. In this chapter, it was observed that children in the Under-11 age category showed better tactical performance in small game’s formats, and greater physical demands, due to the greater involvement of the players. In this sense, it seems that the use of the F-11 game format in competitions of the U-11 age category can result in an increase in the complexity of the game, and negatively impact the individual and collective tactical performance. In Chapter II, it was investigated how different competitive contexts impact on the dynamics of space occupation and the physical performance of four teams, for this, the simulated competition games were analyzed concomitantly with the games of the official competition of the Associação Amazonense de Futebol - FAF. Thus, it was identified that the decrease in the individual area per player (AIJ) restricted space exploration, while the greater number of players favored greater occupation of the teams' space and reduced the physical intensity of the actions. In this sense, it seems that the lowest AIJ of the official competition inhibits the exploration of space by the players. On the other hand, in the F-5 and F-7 formats, the matches motivated the teams to adopt a positioning that favors the implementation of a more direct offensive game method. Therefore, based on the results of the studies, we show that different actions and behaviors can emerge in the different competitive contexts analyzed and we propose some guidelines to adjust the size of the field in competitions of the U-11 age category. In this way, sports federations and institutions will be able to propose the creation of more representative competition scenarios for children.
Analysis of youth soccer competitions: influence of game formats on physical performance and tactical behavior in under-11 category
Keywords: Futebol infantil - Análise; Futebol; Esportes; CIENCIAS DA SAUDE: EDUCACAO FISICA; Esporte; Competição; Performance; Infância